O pedagogo especialista em educação : origem e extinção na política educacional brasileira - Almeida, Ana Luiza Melo de (2009)
The transformation process that happened in the last few decades reached all spheres of society, specially the labour areas, and lunged all professional categories by changing its basis of organization, structure and knowledge construction resulting in adjustments and even extinction of some areas. These events had been also affecting the educational counselor workers. This study attempts to investigate the origin and extinction of the pedagogue specialist (also known as educational technician) based on the 5.540/68 Law and 252/69 Article, Brazilian Official Legislation, which created the pedagogue specialist professional function as consequence of the implementation of the Pedagogy Educational Course qualification and also because of the successive educational reforms which proposed the pedagogue specialties extinction, by the modifications influence of the capitalism production system as well as in the world work market. The main methodology used in this study was based on the qualitative bibliographic research with special emphasis on the Marx thought and other studious related to the thematic. We use documental resource, like official legislation, legal advices and resolutions, thematic associate literature, and a field research to improve our knowledge and methodological effort. The field research development was based on a qualitative approach by the use of semi-structure questionnaire applied to pedagogues specialists, who teaches or used to teach at the Universidade Federal de Sergipe. From the dialectical historic materialism, the analysis made by the literature field, documentary resources and dataset collected from the teachers questionnaires showed that the origins of the education pedagogue specialist had strong ties both with the formation process included in the formation policies developed by the Pedagogy Course, as well as the dictatorship political context that emphasized the education system as a realm of economic development. As we analyzed the CNEP/CP nº. 1 resolution, from may 15 of 2006, which establishes for the Pedagogy curriculum guidelines, we could realized that the current process of pedagogue formation is based on government dictates of construction of a trader with new skills and ability, which, unlike the fragmented and rigid division of labor, be able to overwhelm the knowledge of their work, mobilizing them to a transformation of their action along the entire teaching-learning process of work. The educational technician function extinction during the pedagogue formation process had it foundation along the educators movement, who claimed during the eighty s teaching as a common basis for the national course of Pedagogy in Brazil, giving order to the work division at school, in general, depending on the political context in which they were created. Regard as essentials functions since the beginning of 1970 s years, nowadays specialists are opposed to the concept of multipurpose workers that s being required. Therefore, it is of fundamental importance to recognize the historical determinants to the articulation and function of the Pedagogue Specialist (Educational Technician) origins and extinction.